Progressive fold and fabric evolution associated with regional strain gradients: a case study from across a Scandian ductile thrust nappe, Scottish Caledonides - Alsop, G.; Cheer, D.; Strachan, R.; Krabbendam, M.; Kinny, Peter; Holdsworth, R.; Leslie, A. (Geological Society London, 2010)
Fold and fabric patterns developed within a major Caledonian thrust nappe in NW Scotland reflect a progressive increase in regional D2 strain towards the basal ductile detachment. Within the upper greenschist to lower amphibolite facies thrust sheet, the main gently east-dipping foliations and SE-plunging transport-parallel lineations maintain a broadly similar orientation over c. 600 km2. Associated main phase, thrust-related folds (F2) are widely developed, and towards the base of the thrust sheet display progressive tightening and increasing curvilinearity of fold hinges ultimately resulting in sheath folds. Secondary folds (F3) are largely restricted to high-strain zones and are interpreted as flow perturbation folds formed during non-coaxial, top-to-the-NW ductile thrusting.These features are consistent with a structural model that incorporates plane strain pure-shear flattening with a superimposed and highly variable simple shear component focused into high-strain zones. The increase in strain over a distance of 30 km across strike is similar to the increasing deformation observed when structures are traced along strike to the north, and which are apparently related to proximity to basement-cover contacts. A U?Pb zircon age of 4156 Ma obtained from a syn-D2 meta-granite confirms that regional deformation occurred during the Scandian phase of the Caledonian orogeny.